Return to physical activity after recovering from COVID-19 - Zborowski, Marek; Mikulec, Anna; Stawiarska, Aleksandra; Baliga, Cezary (Journal of Education, Health and Sport, 2023)
Introduction Physical activity is the basis of a healthy lifestyle. The COVID-19 pandemic and the disease caused by the SARS-CoV-2 virus seriously burden the human body, which is a direct cause of a long-term return to high physical fitness. Weakness after infection may persist for many weeks, which is associated with a decrease in the efficiency of athletes, both at the amateur level and characterized by a high level of training. Aim The aim of the study was to determine the occurrence of difficulties related to returning to physical activity after recovering from COVID-19. Material and methods The research tool was a questionnaire consisting of single and multiple-choice questions regarding issues related to practicing physical activity, being ill with COVID-19 and difficulties resulting from returning to fitness before the disease. Results The respondents were dominated by men aged 18-30 undertaking planned physical activity (runners). The analysis of the data showed that most of the participants were characterized by daily physical activity for which they spend 1-2 hours a day. Among the respondents, 69% declared being vaccinated against COVID-19. Data analysis showed that 70% of the respondents suffered from COVID-19, which resulted in fatigue and increased body temperature. The time to return to physical activity after the infection cleared up took mainly 2 to 4 weeks. Conclusions Return to physical activity after recovering from COVID-19 should be skillfully planned, taking into account optimal regeneration and nutrition of the body. The intensity of aerobic training units should be increased gradually so as not to lead to hyperventilation of the lungs. Return to activity should be preceded by medical examinations.